2012
DOI: 10.1210/jc.2012-1411
|View full text |Cite
|
Sign up to set email alerts
|

Role of 11βHSD Type 2 Enzyme Activity in Essential Hypertension and Children with Chronic Kidney Disease (CKD)

Abstract: We have elucidated a functional deficiency of 11β-hydroxysteroid dehydrogenase type 2 in children with CKD and a subset of essential hypertension. Urinary 5α-THF, 5β-THF, and THE analysis by gas chromatography/mass spectrometry should be a part of routine work-up of CKD and hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…These pathogenesis might be involved in kidney diseases in chronic hypercortisolemic states [7,20]. A functional defect in the ability to convert cortisol to cortisone existed in patients with essential hypertension and chronic kidney diseases (CKD), which would result in the activation of mineralocorticoid receptor [21]. MR antagonists not only improve the prognosis for patients with cardiovascular diseases, but also been used in patients with CKD due to its potential effects on reducing proteinuria and kidney damage [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…These pathogenesis might be involved in kidney diseases in chronic hypercortisolemic states [7,20]. A functional defect in the ability to convert cortisol to cortisone existed in patients with essential hypertension and chronic kidney diseases (CKD), which would result in the activation of mineralocorticoid receptor [21]. MR antagonists not only improve the prognosis for patients with cardiovascular diseases, but also been used in patients with CKD due to its potential effects on reducing proteinuria and kidney damage [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Family studies have shown that 20- 40% of cases seen are genetically determined. Different monogenic causes of PH have been established including mutations in the corticosteroidogenic genes, CYP11B1, and HSD11B2 28-30 , mutations in the epithelial sodium channel (SCNN1B, SCNN1G), in the WNK serinethreonine kinase, 31,32 and polymorphisms in the renin-angiotensin-aldosterone system (RAAS) 30,33,34 . However, pure monogenic causes of PH are still rare.…”
Section: Risk Factors For Essential Hypertensionmentioning
confidence: 99%
“…5 Furthermore, we examined whether augmented GC activation in CKD relates to impaired glucose handling.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described a correlation between loss of renal function and GC activation by 11β-HSD enzymes, measured as a rise in the ratio of cortisol/cortisone or a rise in the ratio of their respective metabolites (tetrahydrocortisol [THF]+5α-tetrahydrocortisol [5αTHF])/ tetrahydrocortisone (THE). 4,5 Due to limitations of measuring steroid metabolism in this way, the relative contribution of each 11β-HSD enzyme to the reported shift in cortisol metabolism is not known. Loss of renal expression of 11β-HSD2 and diminished cortisol inactivation likely plays a role.…”
Section: Introductionmentioning
confidence: 99%